νόσος and δσίη: etymological and sociocultural observations on the concepts of disease and divine (dis)favour in ancient Greece - Willi, A (Cambridge University Press, 2008)
After a brief discussion of earlier etymological theories, this article proposes a new analysis of the Greek noun νόσος 'disease' as a possessive compound *n-osw-os 'not having *(h₁)osu', the second constituent of which is cognate with Hitt. āssu 'well-being'; just like the latter, Greek νόσος are characteristically sent or removed by divinities. Moreover, the reconstruction of an abstract noun *(h₁)osu 'well-being (resulting from divine favour)' can serve as the etymological basis for the somewhat obscure Greek notion of δσίη, which refers to the state of something that is endowed with such *(h₁)osu; in fact, phraseological parallelisms between texts from various parts of the Greek world as well as ancient Anatolia point to a common conceptual framework behind all these words.